A influência do porte no desempenho logístico das empresas usuárias do drawback - Konda, Sussumo Tatenauti (2008)
The use of government duty assistance, like drawback, can be, at first time, always be advantage without considering the firm size. However, many different factors inside and outside of the organization interfere on its use. With the proposal of analyse the influence of the company size on the performance of logistic integrations management activities on the company that used drawback, it has been done a research including two steps based on theory of logistic knowledge and small firm internalization authors. The first, considered of exploratory nature, was used a sample compound of 3 companies. The information collected was treated by the content analysis and the result understood more of: a) drawback practice; and b) drawback s effects on logistic performance. Based on these results started the second stage, which was of descriptive nature research. The sample contained of 136 companies of different sizes, chosen for convenience. At these step the collected information had been treated through descriptive and inference statistics and as a result appeared differences in stages of logistic integration management, supply, manufacture and distribution, as well as advantage, disadvantage, block and facility elements on company that used drawback. The analyses provide, also, the information that new companies failed to apply the drawback due to the complexity and weakness of specialized providers of knowledge. The data results permitted the affirmation that company s size influenced the performance of logistic integration management activities, with the drawback users. Finally, as a suggestion, the proposal of this research could be continued studied by increasing: a) the sample group with other sectors of Brazilian s industrial companies; and b) the research with small companies in order to understand more about the drawback s advantage in this group.